Continuing the Red Roots and Practicing Practical Education ——Practice and Theoretical Construction of Red Research and Study at Harbin Jihong Primary School - Xin Sun; Ning Yu (Education Research on Study Tours and Practice, 2026)
Red research and study serves as a core pathway for fulfilling the fundamental task of fostering morality and cultivating people, as well as deepening practical education in the new era. Rooted in the profound red cultural heritage of Heilongjiang Province, Harbin Jihong Primary School has systematically constructed a red research and study system since 2023. In 2023, it launched the "First Heilongjiang Research and Study Train" with the theme of "Casting Souls at the National Border"; in 2024, it went deep into the Great Northern Wilderness under the theme of "Tracing Footprints"; in 2025, it headed to Daqing with the theme of "Iron Man Spirit", forming a progressive education chain of "Three Themes in Three Years". From three dimensions—strategic educational value, theoretical framework and practical paths—this paper systematically elaborates on the contemporary significance and implementation experience of red research and study at Jihong Primary School, and refines the "1-2-3-4" red research and study education model, so as to provide theoretical reference and practical samples for red education and practical education in primary schools in the new era.